Petrology, geochemistry, and geochronology of the leucogranites in southernmost Finland - Saukko, Anna; Nikkilä, Kaisa; Eklund, Olav; Fröjdö, Sören; Väisänen, Markku (The Geological Society of Finland, 2025)
In the southernmost part of the Svecofennian province in Finland, leucogranites and migmatites stemming from both igneous and sedimentary protoliths reflect the complex magmatic history of the Svecofennian orogeny between 1.89 and 1.82 Ga. Although the migmatites and leucogranites in southernmost Finland display similar ages as their counterparts elsewhere in the Southern Finland Subprovince, they differ in field appearance and composition. Field and petrographical observations reveal K-feldspar megacrysts of varying sizes in the migmatized early Svecofennian (c. 1.89–1.87 Ga) supracrustal rocks and granitoids. Whole-rock geochemical analyses likewise display anomalously high K-contents in the early Svecofennian granitoids. Zircon U-Pb dating of migmatites and related leucogranites shows that a late Svecofennian partial melting event occurred at 1.84–1.82 Ga, possibly in several pulses. The morphological features of the migmatites as well as neosome mineralogy indicate a formation mechanism different from the dehydration melting prevalent elsewhere in the Subprovince.